Pre‐transplant Social Adaptability Index and clinical outcomes in renal transplantation: The Swiss Transplant Cohort study. Issue 4 (6th March 2021) - Denhaerynck, Kris; Goldfarb‐Rumyantzev, Alexander S.; Sandhu, Gurprataap; Beckmann, Sonja; Huynh‐Do, Uyen; Binet, Isabelle; De Geest, Sabina
Abstract: Background: The impact of pre‐transplant social determinants of health on post‐transplant outcomes remains understudied. In the United States, poor clinical outcomes are associated with underprivileged status, as assessed by the Social Adaptability Index (SAI), a composite score of education, employment status, marital status, household income, and substance abuse. Using data from the Swiss Transplant Cohort Study (STCS), we determined the SAI's predictive value regarding two post‐transplant outcomes: all‐cause mortality and return to dialysis. Methods: B etween 2012 and 2018, we included adult renal transplant patients (aged ≥ 18 years) with pre‐transplant assessment SAI scores, calculated from a STCS Psychosocial Questionnaire. Time to all‐cause mortality and return to dialysis were predicted using Cox regression. Results: Of 1238 included patients (mean age: 53.8 ± 13.2 years; 37.9% female; median follow‐up time: 4.4 years [IQR: 2.7]), 93 (7.5%) died and 57 (4.6%) returned to dialysis. The SAI's hazard ratio was 0.94 (95%CI: 0.88–1.01; p = .09) for mortality and 0.93 (95%CI: 0.85–1.02; p = .15) for return to dialysis. Conclusions: In contrast to most published studies on social deprivation, analysis of this Swiss sample detected no significant association between SAI score and mortality or return to dialysis.